2014
DOI: 10.3109/0886022x.2014.917575
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic uremic syndrome associated withAcinetobacter hemolyticus

Abstract: Shiga toxin-producing Escherichia coli and Shigella dysenteriae have been associated with bloody diarrhea and hemolytic uremic syndrome (HUS) in humans. However, there have been only a couple of reports describing bloody diarrhea associated with Acinetobacter spp. and there are no reports of these bacteria causing HUS in children. Here, we report the case of a nine-month-old boy with bloody diarrhea who developed non-oliguric renal failure. The clinical and laboratory findings supported the diagnosis of Acinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Besides, several previous studies have revealed that Bifidobacterium and Lactobacillus are significantly decreased in CKD and uremia (Bobrov & Karpov, 1993;Miu, Bilev, & Iua, 2008). Acinetobacter is associated with hemolytic uremic syndrome (Da & Lipinski, 2014), and B. cereus is another motile, aerobic and Gram positive bacterium associated with hemolytic uremic syndrome (Oroujzadeh, Gholivand, & Jamalabadi, 2017), which are consistent with our findings. In the current study, Gubenxiezhuo dialysis could significantly attenuate the upregulation of Acinetobacter, B. cereus, P. vulgaris, S. flexneri, and E. coli, and the downregulation of Bifidobacterium, Lactobacillus and…”
supporting
confidence: 92%
“…Besides, several previous studies have revealed that Bifidobacterium and Lactobacillus are significantly decreased in CKD and uremia (Bobrov & Karpov, 1993;Miu, Bilev, & Iua, 2008). Acinetobacter is associated with hemolytic uremic syndrome (Da & Lipinski, 2014), and B. cereus is another motile, aerobic and Gram positive bacterium associated with hemolytic uremic syndrome (Oroujzadeh, Gholivand, & Jamalabadi, 2017), which are consistent with our findings. In the current study, Gubenxiezhuo dialysis could significantly attenuate the upregulation of Acinetobacter, B. cereus, P. vulgaris, S. flexneri, and E. coli, and the downregulation of Bifidobacterium, Lactobacillus and…”
supporting
confidence: 92%
“…Correspondingly, we found that after DF intervention, the abundance of some potential pathogenic bacteria decreased. These species included Acinetobacter and Ruminococcaceae , which are related to infection, hemolysis and anorexia nervosa [ 34 , 35 ]. However, we found that the relative abundance of Blautia, which is a BA-producing bacterium, was decreased in the DF group, but the serum BA level was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, E. coli and S. dysenteriae type-1 strains are considered to be the major carriers of Shiga toxins; however, these toxins have also been described in several other bacterial genera and species, including Shigella flexneri, Shigella sonnei, Citrobacter spp., Aeromonas spp., Acinetobacter haemolyticus, Salmonella spp., Vibrio vulnificus, and Campylobacter spp. [58][59][60][61][62][63][64][65][66][67], among others, with each of these representing emerging and growing public health risks.…”
Section: Shiga-toxin-producing Bacteriamentioning
confidence: 99%
“…For instance, in 2006, Grotiuz [64] reported the first Stx2-positive Acinetobacter hemolyticus strain from an infant with bloody diarrhea. Later, in 2014, another Stx-positive A. hemolyticus strain was identified as the causative agent of HUS in a 9-month-old infant [65]. Beyond Acinetobacter, after screening 278 bacterial isolates that were positive for the eae gene, Ooka et al [66] identified two strains of E. albertii, one isolated from a diarrheal patient and the other from a healthy bird, that harbored an stx2 gene belonging to the stx 2f subtype.…”
Section: Other Bacteriamentioning
confidence: 99%